Perempuan dan Agama Dalam Novel Dunia Kecil Yang Riuh Karya Arafat Nur - Wati, Serly Enzellina; Murniviyanti, Liza; Armariena, Dian Nuzulia (Indonesian Research Journal on Education, 2023)
This research aims to gain an in-depth understanding of "women and religion in the novel Dunia Kecil yang Riuhuh by Arafat Nur, through psychoanalytic studies". There is also a method used in this research a qualitative method to explain and describe the results of the analysis of the novel Dunia Kecil yang Riuh Karya Arafat Nur. The problem of this research is how the figure of women is depicted in the novel DuniaKecil yang Riuhuh Karya Arafat Nur in terms of the novel and the Islamic psychoanalysis system.Therefore, the purpose of this study is to gain an in-depth understanding of "women and religion in the novel Dunia Kecil yang Riuhuh Karya Arafat Nur through psychoanalytic studies". The source of data obtained in the novel Dunia Kecil yang Riuh Karya Arafat Nur. Data collection techniques in this research are reading and listening techniques. The results and discussion in this study are related to psychoanalysis of women and religion in terms of the theme and background of the character and the mandate that can be taken about the spread of religion in Parengan Village, which used to be ignorant of religion to become more embracing of Islam.